Additive manufacturing of dental root-analogue implant with desired properties. (6th December 2021) - Li, X.C.; He, L.; Zhang, J.W.; Misra, R.D.K.; Liu, S.L.; Xiong, Z.H.; Tang, Z.H.
ABSTRACT: Selective laser melting (SLM) was used to process commercially pure titanium (Grade 1 ELI CP Ti) dental root-analogue implant (RAI) with oval cross-section abutment (OCSA) design. The RAI was tested with a fatigue test system according to ISO 14801, maximum compression load is 350 N, 450 N and 500 N, the load tilt angle is 30°, R = 0.1. To simulate the stress distribution of implant and alveolar bone, a finite-element model was established. The elastic modulus of implant materials was set to 90 GPa and 110 GPa to simulate CP Ti and Ti-6Al-4V, respectively. 300 N vertical or 300 N vertical/50 N horizontal occlusal loading was applied. The biomechanical behaviour of peri-implant bone was recorded. Fatigue strength of RAI sample was 500 N. The simulation results showed that at 300 N vertical loading or 300 N vertical/50 N horizontal loading, compared with Ti-6Al-4V, CP Ti had lower von Mises stress on implant and abutment which reduces the risk of failure compared to their respective strength levels; meanwhile, higher von Mises stress on alveolar bone reduces stress shielding. The study underscores that the CP Ti and SLM are favourable for the fabrication of RAI.